Perbandingan Prevalensi dan Kematian Ileus Paralitik dengan Kanker Usus Besar di Indonesia: Analisis Data Global Burden of Disease (GBD) Tahun 2019, 2021, dan 2023 - Irma Nurvita Zerlinda; Vita Widyasari; Titik Kuntari (Universitas Muhammadiyah Manado, 2026)
Colorectal cancer and paralytic ileus are significant health concerns worldwide, including in Indonesia, where their prevalence and mortality rates have shown concerning trends. This study aims to compare the prevalence and mortality of paralytic ileus and colorectal cancer in Indonesia using data from the Global Burden of Disease (GBD) for the years 2019, 2021, and 2023. A secondary data analysis was conducted using GBD 2023 data, focusing on prevalence, incidence, and mortality rates for both conditions across 34 provinces in Indonesia. The study employed a time-trend analysis to observe the changes in disease burden over the specified years, along with examining the differences in disease characteristics based on sex, age groups, and regions. Results indicated that colorectal cancer has a higher burden of disease, with significantly higher prevalence and mortality rates compared to paralytic ileus. This highlights the urgent need for enhanced prevention, early detection, and management strategies for colorectal cancer in Indonesia. The findings emphasize the importance of integrated healthcare policies to address both conditions effectively, focusing on regions with the highest disease burden. Further research is recommended to explore the underlying risk factors and to evaluate the effectiveness of current healthcare interventions.